Problems of staff training for the library local history - L. G. Taranenko (Библиосфера)
Training the local history specialists in libraries is an urgent problem of our time. The required core competencies for local history staff training are partially laid down in the educational and professional standards. The study objective is a comprehensive analysis of educational institutions that provide training, retraining and advanced training the library specialists. The research includes three stages: 1. Sites analysis of universities training according the direction «Library-information activities» (2016). The results have been presented earlier. 2. Sites analysis of secondary professional educational institutions training on the specialty «Library Science». 3. The analysis of institutions and organizations involved in retraining and advanced training staff for the library local history. The results of sites analysis of secondary professional institutions have revealed 15 institutions, which curricula include the disciplines of local history problematics. The analysis of database «Institutions of Library Education» generated by SPSTL SB RAS made it possible to determine the main list of organizations engaged in retraining and raising the professional skill level of library specialists. It was determined that information on the professional development of local history specialists is not available on official websites of educational organizations. The paper reveals the following significant problems in training the local history specialists: curricula closeness of secondary professional and higher educational institutions in providing the information on local history studies; lack of comprehensive information on institutions involved in direct retraining and professional development of such specialist; weak response of educational organizations of library education and structures of additional vocational education to the modern requirements of library practice in their training. The authors has concluded that it is necessary to coordinate the work between educational institutions, libraries and professional association - RLA.